MEDIA BLACKOUT IN INDONESIAN CRIMINAL JUSTICE SYSTEM: HOW SHOULD IT BE FORMULATED? - Peter Jeremiah Setiawan; Elfina Lebrine Sahetapy; Bhanu Prakash Nunna (Diponegoro Law Review, 2026)
Indonesia’s criminal justice system recognizes closed court hearings, yet it lacks a media blackout mechanism capable of restricting the dissemination of case information beyond the courtroom. This normative gap weakens the protective purpose of closed proceedings because victims’ identities, evidentiary materials, and sensitive information may still circulate through journalistic and non-journalistic media. This article examines how a media blackout should be formulated within Indonesia’s criminal justice system. Using a doctrinal method, the study analyzes legislation, legal doctrine, human rights principles, victimology, and comparative practices from the United Kingdom, Canada, and Australia. The analysis finds that a media blackout should be treated as an exceptional restriction on freedom of expression, access to information, press freedom, and the right to a fair and open trial. Its application should therefore be limited to three fundamental grounds: protection of national security and confidential state information; protection of victims, particularly children and victims of sexual violence; and protection of law-enforcement or criminal-justice interests. The blackout may take the form of temporary or permanent restrictions on publication concerning subjects or proceedings. To prevent arbitrariness, its implementation should require prior judicial authorization and provide an objection mechanism through pretrial proceedings. Courts should apply necessity and proportionality tests to determine whether no reasonable alternative can prevent serious harm and whether the protective benefits outweigh the adverse impact on individual rights, press freedom, open justice, and effective criminal adjudication.